Ritual Communication Behind Nyerabi Tradition (Symbolic Quran Recitation of the Wali Nyatok Preaching at Rembitan Ancient Mosque, Lombok) - Salim, Abdul (Universitas Syiah Kuala, 2024)
Nyerabi is a special ritual for the Islamic community in Rembitan. In this research, we will review the meaning and traditions of nyerabi in the ancient mosque of Rembitan Village, Pujut District, Central Lombok Regency. This research aims to determine the symbolic meaning and traditions of the Rembitan Village community in the form of rituals. In particular, later the results of this research can be described in terms of its aims and objectives. This research uses descriptive qualitative methods. Data collection techniques using observation, interviews and documentation. This research will provide understanding and knowledge about the Nyerabi ritual tradition and the use of symbols and cultural and religious elements in the Nyerabi ritual tradition.